Taxonomic studies on Indian Tropobracon Cameron (Hymenoptera: Braconidae: Braconinae), with descriptions of two new species - Haider, A. A.; Ahmad, Z.; -, Shujauddin (Zootaxa, 2004)
The paper deals with the Indian species of Tropobracon Cameron (Hymenoptera: Braconidae: Braconinae). Two new species, namely, Tropobracon hayati Haider sp. nov. and Tropobracon shafeei Haider sp. nov., are described, while Tropobracon comorensis Achterberg and Tropobracon infuscatus Achterberg are reported for the first time from India. Material pertaining to T. luteus Cameron are also recorded and a key to the Indian species is given.